SARANG LEBAH SEBAGAI IDE PERANCANGAN DAYBED - Muhammad Fadlun Nizar (SULUH: Jurnal Seni Desain Budaya, 2020)
Honey bees are often called the architect insect in nature whichis amazing. The nests are made in the form of a hexagonal (hexagonal) cell arrangement. This then triggered theemergence of an idea to create a representation in the form of a furniture product by applying honey bee hives as an idea todesign a bale-bale daybed. Daybed / bale-bale not only carries a philosophical meaning. Based on this, the problems raised inthis case are (1) How to make a Daybed / Bale-Bale that is able to support human activities, (2) How to apply the form ofbeehive into Daybed / Bale-bale products. (3) How to make an innovative Daybed / Bale-bale pedestal panel.